2018
DOI: 10.5812/semj.81243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Evening Primrose Oil and Vitamin B6 on Pain Control of Cyclic Mastalgia Associated with Fibrocystic Breast Changes: A Triple-Blind Randomized Controlled Trial

Abstract: Background: Mastalgia is the most common symptom of fibrocystic breast changes. It causes concern and fear of breast cancer and has negative effects on quality of life. The study aimed to compare the effectiveness of evening primrose oil (EPO) and vitamin B6 in the pain control of cyclic mastalgia. Methods: This triple-blind randomized controlled clinical trial was conducted on 94 patients with mastalgia referring to the breast clinic of Milad hospital, Tehran, Iran. The participants were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…The results showed that both evening primrose oil (EPO) and vitamin B6 decreased breast pain, but vitamin B6, as a cheaper and more easily available agent, was shown to have significantly better pain-reducing effects (P < 0.001 and CI = 95%). In the placebo group, there was no significant reduction in breast pain (P = 0.815) (21). Paine score (0-3)…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…The results showed that both evening primrose oil (EPO) and vitamin B6 decreased breast pain, but vitamin B6, as a cheaper and more easily available agent, was shown to have significantly better pain-reducing effects (P < 0.001 and CI = 95%). In the placebo group, there was no significant reduction in breast pain (P = 0.815) (21). Paine score (0-3)…”
Section: Resultsmentioning
confidence: 92%
“…Mean baseline pain scores were 1.51 in control and 1.67 in the intervention group, showing 0.75 and 0.61 reduction after treatments, respectively (P < 0.01) (20). Jahdi et al (2018) compared the effects of vitamin B6 and evening primrose. Thirty-one women (18 -50 years old) received 50 mg vitamin B6 twice daily for three months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some sources consider right daily intake of evening primrose oil about 8 g for adults and 4 g for children [ 22 , 23 , 25 , 38 , 39 ]. In terms of side effects and safety of evening primrose in humans, although it is usually well tolerated and no significant side effects have been documented in the medical literature, it has been recommended that using evening primrose oil during pregnancy should be avoided [ 14 , 40 ].…”
Section: Discussionmentioning
confidence: 99%